Problematics and implementation of the literacy movement - Nugrahaeni, Rizky Dwi; Wiarsih, Cicih (Research in Education and Technology (REGY), 2023)
The literacy movement faces several challenges in its implementation, especially the literacy movement in Indonesia. This literature study aimed to analyze the problems and implementation of the literacy movement in Indonesia using the literature study method. Data was collected by searching articles and journals related to the literacy movement in Indonesia. The results of the analysis showed that the government plays an important role in increasing public interest in reading through various programs and policies that support the literacy movement. However, there are still obstacles to implementing the program, such as a lack of budget and a lack of coordination between the agencies involved. In addition, the importance of considering local wisdom in developing literacy programs in Indonesia was also emphasized. The role of the family and school in increasing literacy is also very important. Other obstacles include the lack of access to reading materials and technology to support literacy, the lack of public awareness of the importance of literacy, and the lack of quality and quantity of human resources related to literacy. In overcoming the problems of the literacy movement, the implementation of effective programs involving the government, educational institutions, families, and society as a whole is very important. The results of this literature study are expected to contribute to the development of the literacy movement in Indonesia.